Synthesis, characterization and antioxidant studies of copper(II) complex with schiff bases derived from 4-hydroxybenzaldehyde / Illuni Hayaty Ahmad - Ahmad, Illuni Hayaty (Faculty of Applied Sciences, 2009)
Three Schiff base ligands were suscesssfully synthesized by condensation reaction of 4-hydroxybenzaldehye with benzylamine, o-phenylenediamine and ethylenediamine in 1:1 and 2:1 ratio yielding 4-hbba, 4-hbopd and 4-hben, respectively. Metal complex of Cu(II) has been isolated with the 4-hbba ligand and all of the synthesized compounds are characterized by infrared spectroscopy, ¹H NMR, magnetic susceptibility and molar conductivity. It is proposed that the synthesized complex [Cu(4-hbba)(OAc)₂]₂.xH₂O, has a tetrahedral geometry. The synthesized compounds have been screened for antioxidant properties by comparing their activities with vitamin C, where the ligands 4-hben and 4-hbopd are found to possess some antioxidation activities.